Buying local brands: factors influencing consumers actual purchase behavior - Alekam, Jamal Mohammed Esmail; Adam, Mohamad Zainol Abidin (2014)
The study empirically investigates the important antecedents: intention, patriotism, trust, family and government support to actual purchase of local brand in the Republic of Yemen.Though a lot of attention is given to study the relationship between key drivers in enhancing actual purchase and intention, patriotism, trust, family and government support.Still, there is a considerable confusion about how this relationship is developed and where it is directed. Each of the construct was measured in 7- point Likert scale ranging from 1 strongly disagree to 7 strongly agree, where actual purchase has 6 items, intention has 8 items, patriotism has 11 items, trust has 8 items, family has 8 items and government support has 8 items.Four hundred self-administered questionnaires were distributed to target respondents among education specialists in Aden, Southern Province, and Northern Sana of Yemen. 252 questionnaires were completed and returned, the response rate was 63%.The data were analyzed using Structural Equation Modeling (SEM) through AMOS 21. The goodness of fit indices of the revised structural model indicates adequate fit (GFI: 0.956, CFI: 0.984, RMSEA: 0.033, Ratio: 1.274, P-value: 0.066).The regression parameter estimates show three significant relationships between intention and patriotism (β=0.244, P-value> 0.002 and C. R=3.039), intention and family ((β=0.692, P-value = P <. 001*** and C.R=7.668), actual purchase and intention (β = 0.786, P –value = P <. 001*** and C.R = 6.904). The results show that purchase intention is positively related to consumer patriotism and family.In addition, the results also indicate that the impacts of purchase intention of the actual purchase are significant. These results are discussed in the context of improving domestic product brand in the Republic of Yemen.